The effect of ziltivekimab on the neutrophil-lymphocyte ratio: analysis from RESCUE. (3rd October 2022) - Adamstein, N; Cornel, J; Davidson, M; Libby, P; De Remigis, A; Jensen, C; Rajan, S; Ridker, P
Abstract: Background: The neutrophil-lymphocyte ratio (NLR), derived from the complete blood count, independently predicts atherosclerotic events and is a potential biomarker for residual inflammatory risk. A previous study showed that interleukin (IL)-1β inhibition reduces the NLR, but whether inhibition with IL-6, a cytokine downstream of IL-1, also lowers the NLR is unknown. Purpose: To evaluate whether ziltivekimab, a monoclonal antibody targeting the IL-6 ligand, dose-dependently lowers the NLR compared to placebo. Methods: The phase II RESCUE trial randomized 264 patients with moderate to severe chronic kidney disease (CKD) and high-sensitivity CRP (hsCRP) >2mg/L in a 1:1:1:1 ratio to placebo or ziltivekimab 7.5 mg, 15 mg, and 30 mg subcutaneously once every four weeks. As previously reported, the trial met its primary endpoint as demonstrated by hsCRP reductions of 4% in the placebo group as compared to 77%, 88%, and 92% at 12 weeks in the ziltivekimab 7.5, 15, and 30 mg groups, respectively. Using RESCUE trial data, we further evaluated the percent change from baseline in the NLR at 12 weeks and sought evidence of correlation between any observed changes in the NLR with changes in other measured biomarkers. Results: Ziltivekimab dose-dependently reduced the NLR starting at week one and sustained through week 12 (Table). The median change in the NLR at 12 weeks, the primary pre-specified endpoint, was −13.5% in the 7.5 mg group, −14.3% in the 15 mg group, and −22.4% in the 30 mg group compared to 1.56% in the placebo group. The estimated treatment difference was −14.6% (p=0.004), −15.3% (p=0.004), and −23.6% (p<0.0001) in the ziltivekimab 7.5, 15, and 30 mg groups respectively. These changes were driven largely by reductions in the absolute neutrophil count with minimal change in lymphocyte count. The change in NLR with ziltivekimab correlated modestly with the changes in hsCRP (R=0.26, p=0.0006), fibrinogen (R=0.18, p=0.02), and haptoglobin (R=0.17, p=0.03), but not serum amyloid A, ApoA1, ApoB, ApoB/ApoA ratio, or traditional risk markers. Conclusions: IL-6 inhibition with ziltivekimab lowers the NLR. The ongoing ZEUS cardiovascular (CV) outcomes trial will assess whether ziltivekimab can reduce CV event rates among individuals with stage 3 to 4 CKD, known atherosclerotic disease, and elevated hsCRP. If ziltivekimab reduces CV risk, it would provide further evidence for critical inter-relationships between bone marrow function and atherothrombosis. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Novo Nordisk